PENERAPAN STRATEGI LESSON STUDY SECARA KOLABORATIF DAN RUTIN UNTUK MENINGKATKAN KINERJA GURU DI SEKOLAH DASAR - Endang Suli Purwaty (Inteligensi : Jurnal Ilmu Pendidikan, 2022)
This study aims to find out how to apply lesson study collaboratively and routinely to improve teacher performance at SDN Kapasan V / 147 Surabaya. This selection is due to the community's need for quality education where schools are required to improve or improve image and service, so that the community believes that schools deserve to be the choice of students, one of which is through the application of collaborative lesson study to improve teacher performance. This research is classroom action research with the subject of research is a teacher at SDN Kapasan V / 147 Surabaya. Based on the results of the study, the implementation of the Lesson Study strategy that is carried out regularly and continuously can improve teacher performance, besides that collaborative implementation can have an impact on providing a positive and significant impact that has an impact on changing the school's vision and mission and on the motivation of school leaders and teachers, as well as the emergence of innovation and improving the quality of learning facilities, and increasing extracurricular activities.